2017
DOI: 10.1186/s40510-017-0162-4
|View full text |Cite
|
Sign up to set email alerts
|

Perception of smile esthetics by laypeople of different ages

Abstract: BackgroundAge is a factor affecting smile esthetics. Three variables of smile esthetics associated with the maxillary anterior teeth and age-related changes have recently received considerable attention: (i) the incisal edge position of the maxillary central incisors, (ii) the maxillary gingival display, and (iii) the presence of a black triangle between the maxillary central incisors. The aim of this study was to evaluate the influence of age on smile esthetic perception based on these three variables in a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
2
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 46 publications
3
69
2
13
Order By: Relevance
“…A similar result was found in a study 22 of the perception of smile attractiveness and its aesthetics standards variations, in which younger evaluators were more critical when judging smiles with diastema. Sriphadungporn and Chamnannidiadha 23 also concluded that age impacts smile perception. However, to Kokich et al 13 the professional evaluators’ years of experience and laypersons evaluators’ age did not influence the aesthetic perception.…”
Section: Discussionmentioning
confidence: 98%
“…A similar result was found in a study 22 of the perception of smile attractiveness and its aesthetics standards variations, in which younger evaluators were more critical when judging smiles with diastema. Sriphadungporn and Chamnannidiadha 23 also concluded that age impacts smile perception. However, to Kokich et al 13 the professional evaluators’ years of experience and laypersons evaluators’ age did not influence the aesthetic perception.…”
Section: Discussionmentioning
confidence: 98%
“…Most of these studies agree that the more specialized training the observer has received, the more sensitive his/her perception of smile esthetics will be [ 1 ]. Age is another important factor in the perception of smile esthetics, so that some irregularities such as gingival smile and black triangles are perceived differently by laypersons of different age groups [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Given the variations in esthetic perception and the fact that the treatment objectives of the dental professional may not coincide with the patients’ expectations, it is essential that the orthodontist is aware and understands patients’ concerns and their criteria for esthetic judgment before starting orthodontic treatment. Patients must be allowed to participate in determining treatment objectives that respond to their own perception in order to produce outcomes seen as adequate by both parties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…La sonrisa es parte importante de la estética del ser humano, y a su vez el componente gingival forma parte de esta al ser percibida durante este gesto (11)(12)(13)(14).…”
Section: Discussionunclassified